2019
DOI: 10.1038/s41416-018-0372-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SIRT1 deacetylase and p53 activation uncouples the anti-inflammatory and chemopreventive actions of NSAIDs

Abstract: Background Nonsteroidal anti-inflammatory drugs (NSAIDs) have been proposed as chemopreventive agents for many tumours; however, the mechanism responsible for their anti-neoplastic activity remains elusive and the side effects due to cyclooxygenase (COX) inhibition prevent this clinical application. Methods Molecular biology, in silico, cellular and in vivo tools, including innovative in vivo imaging and classical biochemical assays, were applied to identify and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…Moreover, Gorski et al17 demonstrated that knockdown of SIRT1 inhibited the growth of cardiomyocytes. Inhibition of SIRT1 increased the activity of the tumor suppressor gene p53 and facilitated the expression of antiproliferative gene p21 18. In this study, miR-29a regulated the expression of SIRT1 by directly targeting to 3’-UTR of its mRNA in HeLa cells.…”
Section: Introductionmentioning
confidence: 55%
“…Moreover, Gorski et al17 demonstrated that knockdown of SIRT1 inhibited the growth of cardiomyocytes. Inhibition of SIRT1 increased the activity of the tumor suppressor gene p53 and facilitated the expression of antiproliferative gene p21 18. In this study, miR-29a regulated the expression of SIRT1 by directly targeting to 3’-UTR of its mRNA in HeLa cells.…”
Section: Introductionmentioning
confidence: 55%
“…The trans-viniferin species and enantiomeric form database was sketched and prepared with the LigPrep, carefully checking the stereocenters. Molecular docking was carried out through the Glide Ligand Docking with a standard precision (SP) according to a well-established protocol [31]. The active site was identified through the Site Map tool and confirmed according to the annotations of the UniProt pig pancreatic alpha amylase entry (AMYP_PIG).…”
Section: Computational Proceduresmentioning
confidence: 99%
“…In a work published in 2019 by Dell'Omo et al of the Milan group, the ability of NSAIDs to determine the inhibition of proinflammatory factors and the activation of the anti-oncogenic p53 / p21 pathway was studied. This study suggests a new strategy for the design of anticancer drugs, through the modulation of the pro-inflammatory cascade [18]. In a retrospective study published in 2018 Desmedt et al show that the intra-operative administration of ketorolac during breast conservative surgery is statistically significantly associated with a reduction of distant recurrences in patients with early breast cancer and increased BMI [19].…”
Section: Iort Delivered With Xoft® Axxent® Ebx™mentioning
confidence: 84%